Role of Corpus Callosum in Global Developmental Delay - K Mounisha; MU Jeevika; BG Mahesh; B Adarsh; KK Nirnay (Asian Journal of Medical Radiological Research, 2020)
Background: Neuroimaging provides essential information as evidence of previous injuries, specific abnormalities that could indicate a group or a particular disease in babies with global developmental delay. The objectives is to assess the difference of corpus callosal size in various regions of the corpus callosum in cases of children with developmental delay and to know the etiology using MRI. Subjects and Methods: My study includes 102 children between 1 to 6 years of age among which 51 children are cases having signs and symptoms of developmental delay and 51 children are controls i.e. healthy babies. They underwent MRI in the Department of Radiology, JJM Medical College, Davangere in whom corpus callosum is imaged on sagittal MR sections and its size is calculated in different regions. Results: Abnormalities of the corpus callosum like thinning and agenesis were observed in 55.5% (N=27) in the study group, and none of the patients in the control group. Partial corpus callosal agenesis was present in 3.9% of patients. Complete agenesis in 3.9% of patients. Thinning of the corpus callosum was seen in 45% of patients who were in the study group. Conclusion: The current study suggests that corpus callosal abnormalities, including brain changes, is useful in knowing the etiology of global developmental delay.